Irc20 Regulates the Yeast Endogenous 2-μm Plasmid Levels by Controlling Flp1 - Jalal, Deena; Chalissery, Jisha; Hassan, Ahmed H. (Frontiers in Molecular Biosciences, 2020)
The endogenous yeast 2-µm plasmid while innocuous to the host, needs to be properly regulated to avoid a toxic increase in copy number. The plasmid copy number control system is under the control of the plasmid encoded recombinase, Flp1. In case of a drop in 2-µm plasmid levels due to rare plasmid mis-segregation events, the Flp1 recombinase together with the cell’s homologous recombination machinery, produce multiple copies of the 2-µm plasmid that are spooled during DNA replication. The 2-µm plasmid copy number is tightly regulated by controlled expression of Flp1 as well as its ubiquitin and SUMO modification. Here, we identify a novel regulator of the 2-µm plasmid, the ATPase, ubiquitin ligase, Irc20. Irc20 was initially identified as a homologous recombination regulator, and here we uncover a new role for Irc20 in maintaining the 2-µm plasmid copy number and segregation through regulating Flp1 protein levels in the cell.